Legal Controls for Solitary Confinement of Inmates and its Psychological, Health and Social Effect on them - alsadi, Rihab; alkhateb, Wafa; Alatrash, Issam (Journal of Legal Sciences, 2023)
The study aimed to identify the legal controls of solitary confinement for inmates and their psychological, health and social effects on them. The study also aims to identify the controls of solitary confinement in accordance with the most prominent international standards, which are the Nelson Mandela rules for the year 2015, in addition to the national legislation, namely the Palestinian, Jordanian, and Qatari. The study also aimed to identify the The psychological, health and social effects of solitary confinement on the inmates, In this study, the researchers used the analytical approach, based on the analysis of international agreements and national legislation to identify the legal controls, and the analysis of the opinions of jurists to identify the effects. The study reached a set of results, which relate to the concept of solitary confinement, the concept of prolonged solitary confinement, and legal controls. For the application of solitary confinement, in addition to the findings of psychological, health and social effects, the study also recommended a set of recommendations related to the need to train workers in correctional institutions on the best way to apply solitary confinement in correctional institutions, and the need for there to be continuous supervision by the competent authorities on correctional institutions to ensure compliance Correctional institutions apply the controls of solitary confinement.